A Review of the Fault Ride Through Requirements in Different Grid Codes Concerning Penetration of PV System to the Electric Power Network - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod; Noor Lina, Ramli (2015)
The growing of Photovoltaic (PV) power generation and integration into the electric power has started to touch on the stability and reliability of the network. As a result, standards have to be defined in guaranteeing a secure and reliable operation of the power system and one of the important topics is the capability of the PV system to ride through fault during the disturbance. This paper provides an overview and comparison study about Fault Ride-Through (FRT) capability requirements in the recent grid codes, which are enforced by transmission and distribution system operators in different Grid Codes (GCs) regarding the penetration of Photovoltaic Power Plant (PVPP) to medium and low voltage level of the network. This study compared the following common requirements such as FRT either Low Voltage Ride-Through (LVRT) or High Voltage Ride Through (HVRT), reactive current injection during and after the fault, restoring active power and frequency variations. In addition, by depending on this comparison and through studying the Malaysian grid standards, there is a similarity to USA standard thus this paper presents a proposal of FRT capability and frequency deviation for the Malaysian electric grid.